A Study on the Students’ Mastery of Expressions of Preferences of English Study Program at STAIN Bengkalis - Mayasari, Wan Julia; Zahraa, Safra Apriani (INOVISH JOURNAL, 2023)
Grammar is one of the language components that should be learned well by students. However, most of students still make a lot of mistakes especially in mastering expressions of preferences ; prefer…to, like ... better than, would rather… than, and would prefer … rather than. The aim of this study is to find out the students’ mastery of expressions of preferences and the easiest and the most difficult pereferences for them to master. Sixteen English education students of the second semester were the samples which they were given a set of multiple choices that they had to answer. The result showed that mean score of the students’ mastery is 60.62 which is classified into fair. The students’ mastery of expressions of preferences is 60.62 which is classified into fair. The easiest preference to master is preference prefer … to (67.96) and it is categorized into fair and the most difficult one is  preference would rather … than (53.56) and it is categorized into poor.